Strategies to reduce dropouts in the basic and higher education - Paulo Fossatti; Hildegard Susana Jung (Universidade Federal de Santa Catarina, 2019)
The theme of this article aims to discuss strategies to reduce dropout rates in the Basic and Higher Education. The objective is to discuss strategies of good practices for the permanence of students. The qualitative-quantitative methodology recovers analysis of literature and documentary analysis of Brazilian government agencies and surveys of world rankings, including quantitative data. The results focus on the following strategies: Valorization of Knowledge from the Experience; Education for the Production of Meaning; Consolidation of Policies of the Ministry of Education (MEC) in the School-University integration; Definition of the Policy of initial and continuing teacher training; Valorization of the Teaching Profession; and Humanization of educational relations. The complexity of the topic requires a wide debate in the involvement of all subjects involved in educational processes. Only with effective public policies in education can we guarantee better rates, percentages and greater added value, tangible and intangible in the educational sphere.